Evaluación de aminoácidos aplicados al suelo y follaje sobre el desarrollo y producción del cultivo del arroz (Oryza sativa L.), en la zona de Babahoyo, Los Ríos. - Campozano Martínez, Alan George (2018)
VIII. SUMMARY The present experimental work was carried out he/she carried out in the sector Las Malvinas of the canton Babahoyo, located to 8,4 km in the road La Ventura-La Macarena. Three sources of amino acids were investigated, in two application forms and two dose of the same ones. The outlined objective was to evaluate the agronomic behavior from the rice to the use of the amino acids under watering, to determine the most effective product. The crop of rice was carried out with the variety F-11 in parcels of 20 m2. The treatments were distributed at random in a design of complete blocks in factorial arrangement and for the evaluation of stockings of treatments the test was used from Tukey to 95 % of probability. The studied variables were: height of plants, macollo number for m2, longitude and number of panicule m2, days to flowering, days to crop, weight of 1000 seeds, yield for hectare, relationship seeds straw, analysis to foliate and economic analysis. The doses of amino acids together with a fertilization program with macroelementos, influenced significantly in the yield and development of the cultivation of rice. The biggest plant height was presented with the use of Agrostemin applied to the floor. Bigger macollo number was achieved applying Enerfol via foliating in the outlined doses. He numbers panicule it was bigger when Enerfol was used with applications foliage in dose of 1 and 2 L/ha. significant difference was presented in days to flowering and it harvests, when Agrostemin was applied via foliating. Bigger panicule size was obtained with to the application of Agrostemin via foliating. The grain weight and grain yield went bigger using Agrostemin to the floor in dose of 2 L/ha. The economic utility was positive and bigger with the use of Agrostemin in dose of 2 L/ha applied to the floor. The analysis to foliate determined levels adapted in all the nutrients except for the Copper. Key words: Evaluation, rice, amino acids, application.